- #1

- 82

- 0

x^2 + y^2 + 2x -12y + 12 = 0

(x-a)^2 + (y-b)^2 = r^2 in that form.

why doesn't this work.

(x+1) + (y-6)

this gives you your x^2 your 2x and a +1 Gives you y^2 and -12y and a +36

so (x+1) + (y-6) + 49 = 0?

that would make r^2 negative which is impossible, what am i screwing up here?

(x-a)^2 + (y-b)^2 = r^2 in that form.

why doesn't this work.

(x+1) + (y-6)

this gives you your x^2 your 2x and a +1 Gives you y^2 and -12y and a +36

so (x+1) + (y-6) + 49 = 0?

that would make r^2 negative which is impossible, what am i screwing up here?

Last edited: